Modification of the Seismic Properties of Subducting Continental Crust by Eclogitization and Deformation Processes. Issue 9 (11th September 2019) - Zertani, Sascha; John, Timm; Tilmann, Frederik; Motra, Hem B.; Keppler, Ruth; Andersen, Torgeir B.; Labrousse, Loic
Abstract: Subduction zone processes and the resulting geometries at depth are widely studied by large‐scale geophysical imaging techniques. The subsequent interpretations are dependent on information from surface exposures of fossil subduction and collision zones, which help to discern probable lithologies and their structural relationships at depth. For this purpose, we collected samples from Holsnøy in the Bergen Arcs of western Norway, which constitutes a well‐preserved slice of continental crust, deeply buried and partially eclogitized during Caledonian collision. We derived seismic properties of both the lower crustal granulite‐facies protolith and the eclogite‐facies shear zones by performing laboratory measurements on cube‐shaped samples. P and S wave velocities were measured in three perpendicular directions, along the principal fabric directions of the rock. Resulting velocities agree with seismic velocities calculated using thermodynamic modeling and confirm that eclogitization causes a significant increase of the seismic velocity. Further, eclogitization results in decreased V P / V S ratios and, when associated with deformation, an increase of the seismic anisotropy due to the crystallographic preferred orientation of omphacite that were obtained from neutron diffraction measurements. The structural framework of this exposed complex combined with the characteristic variations of seismic properties from the lower crustal protolith to the high‐pressure assemblage provides the possibility to detect comparable structures at depth in currently active settings using seismological methods such as the receiver function method. Key Points: Eclogitization of continental crust increases seismic velocities (isotropic averages up to 8.21 km/s) and decreases V P / V S ratios by ~0.04 Eclogitization coeval with deformation causes a high P wave anisotropy of up to 9% Shear zone formation coeval with eclogitization causes changes of the seismic response of the structure